Determining the Thickness Coating of Grinding Powders of Synthetic Diamond Based on a Specific-Surface Approach and using an Extrapolation-Affine 3D Model of Grain - Petasyuk, Grigrii A. (Journal of Coating Science and Technology, 2022)
: Methodological features of indirect determining of thickness coating of grains grinding powders of synthetic diamond are analyzed. A newly revised classification of known methods for determining the thickness of the coating is proposed. The prospects of the methods based on the application of an external specific surface are noted. A positive feature is the proposal to determine the thickness of the coating separately for each grain of the sample, followed by the generalization of the results by calculating the arithmetic mean. This calculation scheme allows you to get more reliable information about the thickness of the coating. The expediency of using an extrapolation-affine 3D grain model in such a calculation scheme is substantiated. Using the extrapolation-affininе 3D grain model allows for determining the thickness of the coating of diamond powder grains without the traditional assumption about the spherical shape of their grains and with less error. For an example of grinding powder AC125 400/315, the advantage of such a 3D model compared to a 3D model in the form of a sphere is proved. The method proposed on the basis of such methodical innovation can be used for powders of other abrasive materials.